Synaptically evoked Ca(2+) release from intracellular stores is not influenced by vesicular zinc in CA3 hippocampal pyramidal neurones - Evstratova, Alesya (Blackwell Science Inc, 2011)
ABSTRACT: The co-release of neuromodulatory substances in combination with classic neurotransmitters such as glutamate and GABA from individual presynaptic nerve terminals has the capacity to dramatically influence synaptic efficacy and plasticity. At hippocampal mossy fibre synapses vesicular zinc is suggested to serve as a cotransmitter capable of regulating calcium release from internal stores in postsynaptic CA3 pyramidal cells. Here we investigated this possibility using combined intracellular ratiometric calcium imaging and patch-clamp recording techniques. In acute hippocampal slices a brief train of mossy fibre stimulation produced a large, delayed postsynaptic Ca(2+) wave that was spatially restricted to the proximal apical dendrites of CA3 pyramidal cells within stratum lucidum. This calcium increase was sensitive to intracellularly applied heparin indicating reliance upon release from internal stores and was triggered by activation of both group I metabotropic glutamate and NMDA receptors. Importantly, treatment of slices with the membrane-impermeant zinc chelator CaEDTA did not influence the synaptically evoked postsynaptic Ca(2+) waves. Moreover, mossy fibre stimulus evoked postsynaptic Ca(2+) signals were not significantly different between wild-type and zinc transporter 3 (ZnT3) knock-out animals. Considered together our data do not support a role for vesicular zinc in regulating mossy fibre evoked Ca(2+) release from CA3 pyramidal cell internal stores.